(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to assess thicknesses of retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) in patients with episodic migraine and to compare data between from patients with migraine and healthy individuals. Material and Methods: The study included 44 eyes (right) of 44 patients with migraine who presented to neurology outpatient clinic and 54 eyes (right) of healthy individuals. In patients with migraine (with identified subtypes), demographic and clinical characteristics, Visual Analog Scale (VAS) and Migraine Disability Assessment Scale (MIDAS) results were recorded. After detailed ophthalmological examination, RNFL and GCC thicknesses were measured with optical coherence tomography (OCT) (Carl Zeiss Meditec AG, Jena, Germany, software version: 6.5.0.773). The values obtained were compared between groups. The correlation between VAS and MIDAS scores and RNFL and GCC thicknesses were assessed. Results: Mean age was 36.05±8.84 years in migraine group and 32.89±10.89 years in control group. Mean time of follow-up was 5.50±3.42 years in patients with migraine. No significant differences were detected in mean RFNL and GCC thicknesses from all quadrants (p>0.05 for all). It was found that VAS and MIDAS scores were negatively correlated to mean RNFL thicknesses in temporal and inferior quadrants (p0.05). Conclusion: In our study, it was found that migraine did not affect in ocular structures of posterior segment such as RNFL and GCC thickness.Keywords: Migraine; retinal nerve fiber layer; ganglion cell complex; optical coherence tomography.